Analysis of medication errors in medicine ward of medical college teaching hospital, Mandya - K. H., Supriya; N. S., Shashikumar; G. M., Prakash; N., Rajeshwari (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Medication errors are one of the most common types of medical error that is seen in hospitalised patients. Since medication error is one of the growing concerns of healthcare issue and have implications on patient safety, the purpose of this study was to identify medication error and in turn would help to create awareness among healthcare professionals and provide safety to the patients. Methods: Study was initiated after obtaining approval from the Institutional Ethics Committee. The study was done for a period of 1 year between June 2016 and May 2017. Clinical data and data regarding the medication that was prescribed, transcribed, dispensed, administered was collected and was analysed for various types of medication errors during the different stages of medication use process. Results: A total of 351 subjects were recruited in the study for assessing medication error. About 2,283 drugs were prescribed among 351 patients. Maximum number of drugs was administered through parenteral route (50.3%). Medication error was most common during the prescribing stage (51.4%) followed by transcribing stage (39.1%), administration stage (6.9%), and dispensing stage (2.6%). On an average 6 drugs were prescribed per patient. Total of about 5411 errors have occurred out of which 98.8% of errors were preventable, 1.2% of errors were non-preventable. Cardiovascular system (21.9%) and endocrine and renal system (21.9%) was commonly affected due to the medication errors. Conclusions: Medication errors are one of the commonest problems of the healthcare system should be identified and documented and their causes should be studied in order to develop systems that minimize the recurrence.